2023
DOI: 10.1371/journal.pone.0282287
|View full text |Cite
|
Sign up to set email alerts
|

Online education and its effect on teachers during COVID-19—A case study from India

Abstract: Background COVID pandemic resulted in an initially temporary and then long term closure of educational institutions, creating a need for adapting to online and remote learning. The transition to online education platforms presented unprecedented challenges for the teachers. The aim of this research was to investigate the effects of the transition to online education on teachers’ wellbeing in India. Methods The research was conducted on 1812 teachers working in schools, colleges, and coaching institutions fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 29 publications
0
10
0
1
Order By: Relevance
“…This finding is consistent with the research results of past studies (Kaur, 2008;Gorsy et al, 2015;Dagar & Mathur, 2016;Kaur, 2017;Ghosh, Adhikari & Das, 2020) which pointed out towards a decent percentage of Indian school teachers have been suffering from different mental health problems. The reasons or types were not investigated here, but they can be attributed to the structural aspects of the school system, burgeoning expectations of society (Kundu & Bej, 2020), transformational teaching (Dayal, 2023), massive changes in teachers' roles in classrooms and teaching methods (Chaudhry & Chhajer, 2023), and regularly increasing assessment pressure (Bhattacharya & Tandon, 2023), especially in the post-National Education Policy 2020 implemented era.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is consistent with the research results of past studies (Kaur, 2008;Gorsy et al, 2015;Dagar & Mathur, 2016;Kaur, 2017;Ghosh, Adhikari & Das, 2020) which pointed out towards a decent percentage of Indian school teachers have been suffering from different mental health problems. The reasons or types were not investigated here, but they can be attributed to the structural aspects of the school system, burgeoning expectations of society (Kundu & Bej, 2020), transformational teaching (Dayal, 2023), massive changes in teachers' roles in classrooms and teaching methods (Chaudhry & Chhajer, 2023), and regularly increasing assessment pressure (Bhattacharya & Tandon, 2023), especially in the post-National Education Policy 2020 implemented era.…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 pandemic in India has aggravated the issue and negatively impacted school teachers' psychological health due to uncertainty, workload, job dissatisfaction, health issues, and multiple roles, according to research (Chaudhry & Chhajer, 2023;Kim et al, 2022;Maggio et al, 2022). For many Indian school teachers, the abrupt introduction of distance learning presented challenges, including the need to adapt new technologies, revise pedagogy, and change the style of evaluation to deliver online education effectively (Bhattacharya & Tandon, 2023;Dayal, 2023). The transition problem for school teachers has become more acute due to societal expectations and the historic National Education Policy 2020, which envisions a major revamp of the educational system (Kundu, Bej, & Mondal, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…higher alcohol consumption, tobacco smoking, physical inactivity, stress, and depression) (Goncalves et al, 2021;Tavolacci et al, 2021;Wang et al, 2020). While among the teaching staff, the challenges associated with physical and mental health, learning new technologies, and ways of working were most often mentioned (Dayal, 2023;McDonough and Lemon, 2022). In agreement with the results of several previous studies reporting changes in smoking and food preferences in relation to COVD 19 risk perceptions (Gold et al, 2021;Kowalczuk and Ge ˛bski, 2021), the findings of the present study show that European respondents changed their smoking and alcohol consumption habits, physical activity, and nutritional consumption behaviour during the first wave of the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…higher alcohol consumption, tobacco smoking, physical inactivity, stress, and depression) (Goncalves et al ., 2021; Tavolacci et al , 2021; Wang et al , 2020). While among the teaching staff, the challenges associated with physical and mental health, learning new technologies, and ways of working were most often mentioned (Dayal, 2023; McDonough and Lemon, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The Covid-19 pandemic has also led to changes in the nature of teacher-student communication (Ali et al, 2021;Dayal, 2023). A study by Schneider and Council (2020) found that the adoption of online platforms has led to an increase in the frequency and variety of communication between educators and students.…”
Section: Literature Reviewmentioning
confidence: 99%